2014
DOI: 10.1016/j.eururo.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-deprivation Therapy and Diabetes Control Among Diabetic Men with Prostate Cancer

Abstract: Background Androgen deprivation therapy (ADT) for prostate cancer is associated with decreased insulin sensitivity and incident diabetes. Few data are available about the effects of ADT on diabetes control among men with diabetes. We examined care for over 7500 men with prostate cancer who had diabetes at the time of diagnosis to assess the effect of ADT on diabetes control, as measured by HbA1c levels and the intensification of diabetes drug therapy. Methods We compared hemoglobin A1c (HbA1c) levels and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 26 publications
(20 reference statements)
7
59
0
Order By: Relevance
“…A meta-analysis showed that higher testosterone levels are associated with lower and higher T2DM risks in men and women, respectively 37 . In addition, androgen deprivation therapy for prostate cancer patients leads to a worsening of T2DM 38 . In our recent study with HFD-fed mice, fasting glucose levels increased after castration, whereas castration did not affect insulin resistance 16 .…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 87%
“…A meta-analysis showed that higher testosterone levels are associated with lower and higher T2DM risks in men and women, respectively 37 . In addition, androgen deprivation therapy for prostate cancer patients leads to a worsening of T2DM 38 . In our recent study with HFD-fed mice, fasting glucose levels increased after castration, whereas castration did not affect insulin resistance 16 .…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 87%
“…Consistent with previously published data, ADT and subsequent hypogonadism resulted in an increase in serum measurements such as total cholesterol level (p=0.01), fasting insulin (p=0.006), and HOMA levels (0.008) by visit 3 without significant physical changes [69,203]. This is a well-recognized phenomenon and long-term implications include increased risk of diabetes, cardiovascular and cerebrovascular disease [141,[225][226][227]. In recognition of previous publications correlating ADT with adverse health effects, a science advisory statement was made from the American Heart Association (supported by Food and Drugs Administration) stating, "It is reasonable, on the basis of the above data, to state that there may be a relation between ADT and cardiovascular events and death" [141].…”
Section: Adt Associated Adverse Effects Within 12 Weekssupporting
confidence: 75%
“…Adherence and changes to diabetes medication were reported in three studies [31,34], as well as information on diabetes-related complications assessed by occurrence of neuropathy, nephropathy and retinopathy [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported an increase in HbA1c after androgen deprivation therapy (ADT) was initiated [33,34] and one study described raised HbA1c levels following diagnosis and treatment (not specified) for breast cancer [31]. One study in gastric cancer showed mixed results according to type of surgical procedure and/or BMI, however the study design was judged to be weak [37].…”
Section: Resultsmentioning
confidence: 99%